2015
DOI: 10.1111/papt.12067
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of continued presence: On the practical consequences of ‘hallucinations’ in bereavement

Abstract: Practitioners should not assume that ECPs are signs of pathology - often they have healing consequences. Where ECPs cause distress, the problem is likely to concern relationship difficulties with the deceased. Therapists can help clients with distressing ECPs by working on the relationship with the deceased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 46 publications
8
36
0
8
Order By: Relevance
“…In this study, the bereaved also expressed how important it was to have the experiences validated by learning that others have had similar experiences (Keen et al 2013). Research exploring the benefits of these experiences has shown that individuals who report them have less loneliness, feel less intense pain from the loss, and believe that they have received guidance or encouragement from the deceased (Hayes and Leudar 2016). Nevertheless, sense of presence experiences are not always healing and may be associated with increased depression or more severe grief in the short-term (Hayes and Leudar 2016).…”
Section: Sense Of Presencementioning
confidence: 88%
See 2 more Smart Citations
“…In this study, the bereaved also expressed how important it was to have the experiences validated by learning that others have had similar experiences (Keen et al 2013). Research exploring the benefits of these experiences has shown that individuals who report them have less loneliness, feel less intense pain from the loss, and believe that they have received guidance or encouragement from the deceased (Hayes and Leudar 2016). Nevertheless, sense of presence experiences are not always healing and may be associated with increased depression or more severe grief in the short-term (Hayes and Leudar 2016).…”
Section: Sense Of Presencementioning
confidence: 88%
“…In the previous theories of grief, experiences such as sensing the presence of the deceased were considered hallucinations, denial mechanisms, or dysfunctional searching (Steffen and Coyle 2010). Hayes and Leudar (2016) argued that sense of presence experiences are not hallucinations because they are not symptoms of an underlying mental health condition, but rather they are rooted in actual experiences of the past relationship history and are not often problematic. Keen et al (2013) discovered multiple themes among people who experienced "a sense of presence," including the experiences being unique and personally distinctive to the deceased and the bereaved's prior beliefs, as well as understandings being congruent with the experienced sense of presence.…”
Section: Sense Of Presencementioning
confidence: 99%
See 1 more Smart Citation
“…Post-bereavement hallucinations may be particularly informative about the mechanisms driving the onset, and offset, of hallucinations, since they typically remit over time. However, although some researchers have theorized about the role of post-traumatic stress in this type of hallucination (Hayes and Leudar, 2016), empirical investigation of stress-related (biological, cognitive or social) responses is missing. In addition, understanding family members' and carer's responses to post-bereavement and other hallucinatory phenomena has received little investigation, but warrants further investigation given existing evidence that the presence of hallucinations in those with Parkinson's disease or dementia is a strong predictor of caregiver stress and nursing home admission (Oh et al, 2015; Cepoiu-Martin et al, 2016).…”
Section: Gaps In the Evidence Base And Directions For Future Researchmentioning
confidence: 99%
“…BHs are reported by 40-70% of conjugally bereaved persons (Byrne & Raphael, 1994;Carlsson & Nilsson, 2007;Datson & Marwit, 1997;Grimby, 1993;Olson, Suddeth, Peterson, & Egelhoff, 1985;Rees, 1971;Schuchter & Zisook, 1993). While a classic term for these experiences is 'hallucination' (Castelnovo et al, 2015;Grimby, 1993;Olson et al, 1985;Rees, 1971), recent research often uses less pathologicallyconnoted terms like 'sense of presence' (Steffen & Coyle, 2010) and 'experiences of continued presence"' (Hayes & Leudar, 2016). The association of hallucinations with mental pathology has a long history, but the link is challenged by studies showing that hallucinations are common in nonclinical populations (Daalman et al, 2011;Larøi, DeFruyt, van Os, Aleman, & Van der Linden, 2005), resulting in a debate of whether hallucinations are pathological per se.…”
Section: Introductionmentioning
confidence: 99%